The Role of Village Apparatus in Overcoming the Circulation of Alcoholic Beverage Consumption and Gambling Among Muslim Youth in Tanjung Gusti Village, Hamlet I, Galang District, Deli Serdang Regency - Ajizah Nurul Fadhilah Siddiq; Salamuddin (Institut Agama Islam Negeri (IAIN) Curup, 2025)
This study explores the role of village officials in Tanjung Gusti in addressing the circulation of alcoholic beverages and gambling among teenagers. It focuses on five key aspects: (1) the role of village officials, (2) contributing factors, (3) community empowerment strategies, (4) program effectiveness, and (5) challenges faced. The study emphasizes the importance of persuasive communication in encouraging the community to avoid alcohol and gambling. Community empowerment is also highlighted as a crucial factor in preventing these issues. Using a qualitative descriptive approach, data was collected through interviews, observations, and documentation. Findings show that village officials actively work with police, parents, and community leaders to reduce alcohol consumption and gambling. Awareness campaigns and seminars have been effective, though financial constraints and behavioral challenges remain obstacles. The study concludes that collaboration between village officials and stakeholders is essential to minimizing alcohol and gambling among teenagers. Strengthening community empowerment and enforcing strict regulations are key to creating a safer environment.